Chemische Entwicklung metallarmer Objekte während der protostellaren Phase - Kaliwoda, Hans Gunter (2008)
First generation stars, so called Population III stars, by definition are those that formed out of the primordial gas mixture, which was composed of hydrogen, helium and very small trace amounts of lithium and beryllium. Due to their singular chemical composition the formation and evolution of Population III stars differed from that of present-day stars. One significant difference during their formation is the absence of today's most important coolants, so that molecular hydrogen plays an essential role as the main cooling agent. Therefore there is a strong coupling between the chemical, thermal and dynamical evolution of the gas. This thesis presents the modelling of the protostellar phase of Population III star formation, starting with an homogeneous, stationary cloud going until the accretion phase using spherically symmetric simulations which include the hydrodynamics, radiation transport in grey approximation, and chemical evolution, for the first time consistently implemented in one model that uses an implicit scheme for the time integration. In a series of model calculations with different initial values the impact of the chemical composition on the evolution of the gas is explored; furthermore a comparison between the primordial and the present day's case is performed using different gas opacities.
Keywords: Hochschulschrift; Strahlungstransport; Hydrodynamik; Population III; Sternentstehung; Numerische Mathematik; Astrophysik